Optimizing Passenger Flow Control and Bus‐Bridging Service for Commuting Metro Lines. (21st April 2017) - Yang, Jingfeng; Jin, Jian Gang; Wu, Jianjun; Jiang, Xi
Abstract: Oversaturated conditions are often observed during peak‐hour periods, especially for commuting metro lines serving as a corridor connecting suburb and urban areas due to its unidirectional passenger flow pattern. System operators are concerned about the amount of passengers accumulated inside station and at platform when train service cannot meet the travel demand. In this article, we tackle the metro system congestion issue and develop a compound strategy integrating passenger flow control and bus‐bridging service, to mitigate overcrowded situation. A two‐stage mathematical modeling procedure is proposed. Stage 1 determines the stations and time periods for taking passenger flow control strategy. Stage 2 identifies the optimal bus‐bridging services. Mixed integer linear programming models are developed to find the demand‐responsive flow control pattern and bus‐bridging services. The proposed passenger flow control and bus‐bridging strategy is applied to a commuting metro line in Shanghai. The results show that the proposed strategy is effective in reducing the number of stranded passengers, releasing the overcrowding pressure, and improving passengers' satisfaction.